2019
DOI: 10.1002/dmrr.3226
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic episodes increase the risk of ventricular arrhythmia and sudden cardiac arrest in patients with type 2 diabetes—A nationwide cohort study

Abstract: Background:The impact of hypoglycaemic episode (HE) on the risk of ventricular arrhythmia (VA) and sudden cardiac arrest (SCA) remains unclear. We hypothesized that HE increases the risk of both VA and SCA and that glucose-lowering agents causing HE also increase the risk of VA/SCA in patients with type 2 diabetes (T2D).Methods: Patients aged 20 years or older with newly diagnosed T2D were identified using the Taiwan National Health Insurance Database. HE was defined as the presentation of hypoglycaemic coma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
6
0
2
Order By: Relevance
“…19 studies confirmed a significant association between hypoglycemia and macrovascular complications (3,4,10,11,14,16,17,18,20,23,26,28,34,36,38,40,43,45,46). The pooled odds ratio was 1.81 (95% CI 1.70-1.94).…”
Section: Meta-analysis Association Between Hypoglycemia and Macro-andmentioning
confidence: 84%
“…19 studies confirmed a significant association between hypoglycemia and macrovascular complications (3,4,10,11,14,16,17,18,20,23,26,28,34,36,38,40,43,45,46). The pooled odds ratio was 1.81 (95% CI 1.70-1.94).…”
Section: Meta-analysis Association Between Hypoglycemia and Macro-andmentioning
confidence: 84%
“…10 Yapılan bazı çalışmalarda hipoglisemi olan hastalarda DM süresi açısından fark gözlenmezken, bazı çalışmalarda DM süresi ile hipoglisemi varlığı arasında ilişki tespit edilmiştir. 7,[11][12][13][14][15][16] Yapılan çalışmalarda hem ciddi hem de hafif hipoglisemi atağı sıklığı insülin kullananlarda yüksek gözlenmiştir. 12,16,17 Bir çalışmada tip 2 DM hastalarında sadece insülin kullanımının hipoglisemi riskini 6,5 kat arttırdığı bulunmuştur.…”
Section: Discussionunclassified
“…The change in phenylalanine in our study might also be a response to the overconsumption of dopamine in RH. Moreover, phenylalanine can be used as an index of cardiovascular disease (CVD) (47). Magnusson demonstrated that the diabetes-predictive amino acid score (derived from tyrosine, isoleucine, and phenylalanine) strongly predicts the risk of CVD in T2DM (48), which appears to be partially mediated by the propensity for atherosclerosis, suggesting that disturbed amino acid metabolism may be a potential link to hypoglycemia and CVD.…”
Section: Other Changesmentioning
confidence: 99%